Localizing the Finnish model for China : developing an engaging student-centred pedagogy training project for Chinese teachers in basic education - Qian, Wendan (2020)
In Finland, future teachers studying in universities are educated with student-centred approaches in order to be more capable of implementing student-centred approaches in their own classrooms. With strong support from scientific research, Finnish universities are taking a leading role in implementing student-centred approaches. Specifically, the curriculum for teacher education is no longer limited to the teacher-directed approaches, but adopts many collaborative approaches including group work, collaborative learning, collaborative writing, presentation, seminar, webinar, student self-evaluation and peer-evaluation and learning diaries etc. This study draws on scientific research on the use of student-centred pedagogy in Finland and China. It focuses on the specific characteristics of Finnish teacher education and the student-centred focus of the teacher education curriculum. It outlines the essential components of Finnish teacher education through reviewing existing researches, which is the basis of developing a student-centred teacher training module for Chinese teachers. On the basis of the critical review of Finnish teacher education and the current educational culture in China, a training module with five themes is developed in this study. The design-based research methodology is used in the study which aims to bridge theoretical researches on student-centred approach and meaningful practices in local settings. According to existing researches, design-based research methodology is a tool for creating systemic design for understanding how theoretical knowledge could be transformed in a contextually-suitable way in a new educational environment. In order to localize a suitable student- centered pedagogy training program for effective changes in Chinses schools, Chinese teachers’ needs and the context of Chinese education system are taken account within the researcher’s agenda in this study. In general, the design process follows a six-step curriculum development process which includes needs analysis, situation analysis, planning goals, course planning and syllabus design, providing for effective teaching and materials, and approaches to evaluation. An important principle in the design is to gradually support Chinese teachers to move from knowing what to knowing how.